Discovery and characterization of a new genotype of Salmonella enterica serovar Bareilly isolated from diarrhea patients of food-borne outbreaks - Park, Nanjoo; Kwon, Joon-Gi; Na, Hongjun; Lee, Sohyun; Lee, Ju-Hoon; Ryu, Sangryeol (Frontiers in Microbiology, 2022)
Since the first food-borne outbreak of Salmonella enterica serovar Bareilly in the UK (2010), it has been recognized as a new type of food-borne pathogen in S. enterica. To detect and characterize this new serovar pathogen in South Korea, a total of 175 Salmonella strains was isolated and 31 isolates were identified as S. Bareilly from various food-borne outbreaks between 2014 to 2018. While pulsed-field gel electrophoresis (PFGE) analysis using XbaI revealed two major groups (A and B) each with two subgroups (A1, A2/B1, B2), average nucleotide identity (ANI), single nucleotide polymorphism (SNP), and in silico multilocus sequence typing (MLST) analyses confirmed only two major groups. Interestingly, extended SNP analysis with 67 S. Bareilly strains from outbreaks in other countries revealed that A group strains between 2014 and 2016 shared a close evolutionary relationship with the strains from outside of South Korea; however, the B group strains in 2018 were located in a separate SNP tree branch. These findings suggest that the A group may share common ancestor with the strains of previous outbreaks in the UK or other countries, while the B group is a new genotype. Comparative virulence factor (VF) analysis between the A and B group strains showed that S. Bareilly in the B group has more various than that of the A group. A comparative biofilm formation assay supports for this, which B group strain GG-21 has higher biofilm formation activity than A group strain GG-07. Antibiotic susceptibility test of 31 S. Bareilly strains revealed high susceptibility to 17 tested antibiotics, suggesting that S. Bareilly can be easily treated by antibiotics.